Rancang Bangun Alat Pemisah Buah Kopi Berdasarkan Tingkat Kematangan Menggunakan Sensor TCS3200 Berbasis Android - Irma Salamah; Mega Muliawati; Mohammad Fadhli (Building of Informatics, Technology and Science (BITS), 2022)
The processing of coffee before it can be drunk goes through a long process, namely harvesting coffee fruits that have matured either by machine or by hand, then processing coffee fruits and drying before they become spindle coffee. Before the roasting process, the coffee fruit is chosen first to be ripe in order to produce the last result of the best coffee process. After the coffee fruit is selected, the next process is stripping the ripe coffee fruit in order to speed up the post-harvest process of the coffee fruit. Harvesting will also affect the quality and taste of coffee, harvesting is usually done when the coffee fruit that has matured physiologically which is characterized by the color of the fruit skin becomes a red color. At the level of maturity of coffee fruits still occurs not simultaneously so that the harvesting process takes a long time. When the harvest period comes, the separation of coffee fruits is still mostly done manually by picking them in a simultaneous way. This simultaneous separation of coffee fruits makes the mixing of coffee fruits that are still raw, half-ripe, and already ripe, causing poor taste quality, that's why the author got the idea to make a tool that can make the coffee harvesting process simpler and more efficient, namely a coffee fruit separator tool based on maturity level aims to find out how the tool performs in detecting coffee fruits based on maturity levels and how performance from a coffee fruit peeler. This tool can produce separate coffee fruits based on the degree of maturity, namely in the category of ripe, half-ripe and unripe. When coffee fruits that are still not separated between ripe, half-ripe and raw, are placed on the conveyor, the TCS3200 color sensor will detect the coffee fruit according to its color. The coffee fruit will be sorted automatically into a container that has been provided which is controlled by a servo motor that has been pre-programmed by Arduino. After the data from the coffee fruit separator has been read by the sensor, the Arduino will send the data to android via bluetooth connection. Furthermore, red coffee fruits or coffee fruits in the ripe category will proceed to the stripping stage. At the stripping stage, ripe coffee fruits will be peeled on a peeling machine controlled by a servo motor